1984
DOI: 10.1016/0035-9203(84)90124-x
|View full text |Cite
|
Sign up to set email alerts
|

Low dosage diethylcarbamazine administered by villagers for the control of timorian filariasis

Abstract: The results of mass treatment using low dosage diethylcarbamazine (DEC) in three small villages in West Flores, Indonesia, endemic for Brugia timori are described. DEC was distributed on a weekly basis by motivated persons in the community to nearly all villagers for 18 months. An educational programme was developed which focused on describing the relationship between microfilaraemia, vector and disease manifestations, the danger of repeated attacks of adenolymphangitis, and the efficiency of DEC in eliminatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…2000). Only very few drug studies, especially with low dosage of DEC, were performed in B. timori endemic areas (Partono et al . 1981, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2000). Only very few drug studies, especially with low dosage of DEC, were performed in B. timori endemic areas (Partono et al . 1981, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…In the treated B. timori infected individuals, the percentage of fever as well as the number of adverse reactions was higher than in W. bancrofti patients. Adenolymphangitis observed in patients treated with both regimens showed that DEC has prominent macrofilaricidal activity that induces local inflammatory responses around dying parasites (Partono et al . 1984).…”
Section: Discussionmentioning
confidence: 99%
“…It would be unfortunate if DEC were discarded for such reasons. In lymphatic filariasis, spreading the therapeutic regimen over weekly low-dose treatments has proved successful at both avoiding sideeffects and eradicating infection (Partono et al 1984;Partono, Maizels & Purnomo, 1989). Although the evidence we have presented argues against the use of steroids to alleviate adverse reactions, it may be that a further understanding of the mode of action of DEC will define accompanying medication and provide acceptable treatment with a drug which is both microfilaricidal and macrofilaricidal for the lymphatic parasites.…”
Section: Discussionmentioning
confidence: 99%
“…However, the side-effects are clearly related to (a) the parasite load (Wilson, 1950;Partono et al 1981;Francis, Awadzi & Ottesen, 1985), with uninfected individuals showing no symptoms at all; and (6) the drug dose. Low-dose therapy avoids the side reactions (Partono et al 1984).…”
Section: Immunological Side-effects Of Dec Administrationmentioning
confidence: 99%